FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN DAN PENAWARAN KERANJANG ANYAMAN BAMBU (Studi Kasus : Pengrajin Keranjang Anyaman Bambu, Kelurahan Jati Utomo, Kecamatan Binjai Utara,Kota Binjai) - Rahma Sari Siregar (Universitas Medan Area, 2017)
The aim of this study was to determine the factors that influence the demand for baskets woven bamboo against income level artisans in the village of Jati Utomo, District Binjai Utara, Binjai, and to determine the factors that affect the supply baskets woven bamboo against income levels craftsmen in the Village Jati Utomo, District of North Binjai, Binjai. The sampling method for craftsmen using census method. The sample of this research was 15 craftsmen woven bamboo baskets and 30 baskets woven bamboo consumers. This research used regression multiplier liniear . the result show factors that affected the demand for bamboo wicker basket is the price of a basket of woven bamboo, another basket prices, and consumer income. The factors that affected the supply of woven bamboo baskets is the purchase price of bamboo, production costs, and profits.Keywords: Demand, Supply, Prices, Woven Bamboo